FRI0143 A randomized, double-blind, phase 3 study demonstrates clinical equivalence of CT-P13 to infliximab when co-administered with methotrexate in patients with active rheumatoid arthritis. (23rd January 2014) - Yoo, D.; Miranda, P.; Piotrowski, M.; Ramiterre, E.; Kovalenko, V.; Prodanovic, N.; Tee, M.; Gutierrez-Ureña, S.; Jimenez, R.; Zamani, O.; Lee, S.; Kim, H.; et al.
Abstract : Background: CT-P13 was developed as a biosimilar product to infliximab (Remicade®), a chimeric monoclonal antibody approved in the European Union in 1999 for the treatment of rheumatoid arthritis (RA), ankylosing spondylitis, Crohn's disease, ulcerative colitis, psoriasis, and psoriatic arthritis. Objectives: To compare the clinical efficacy and overall safety of CT-P13 with those of infliximab in patients with active RA. Methods: Six hundred six patients with active RA despite previous treatment with disease-modifying anti-rheumatic drugs including methotrexate were randomized 1:1 to receive either CT-P13 or infliximab (3 mg/kg, 2-hour IV infusion per dose) plus methotrexate and folic acid. The treatment period consisted of a dose-loading phase (weeks 0, 2, and 6) and a maintenance phase (weeks 14, 22, and 30). The primary endpoint was the proportion of patients achieving 20% improvement in ACR20 at week 30. The exact binomial test with 95% confidence intervals (CIs) for ACR20 within a margin of ±15% was used to define equivalence between the 2 treatments. Secondary efficacy and safety endpoints (including ACR50/70; frequency of adverse events [AEs]) were also evaluated. This report presents results up to study week 30 (as approved by the European Medicines Agency). Results: At week 30, ACR20 response rates were 60.9% for CT-P13 vs 58.6% for infliximab (2% difference; 95% CI -6% to 10%) in the intent-to-treat population, and 73.4% vs 69.7% (4% difference; 95% CI: -4% to 12%) in the per-protocol population. Outcomes for the secondary efficacy and safety endpoints were also comparable as follows. ACR50 rates in the per-protocol population were 42.3% vs 40.6% (2% difference; 95% CI -7% to 10%), and ACR70 rates were 20.2% vs 17.9% (2% difference; 95% CI -5% to 9%) in the CT-P13 and infliximab arms, respectively, all indicating equivalence in clinical efficacy at week 30. AEs considered by the investigators to be related to study treatment were reported for 106 (35.2%) patients and 108 (35.9%) patients in the CT-P13 and infliximab arms, respectively. Related AEs due to infection were reported in 46 (15.3%) patients and 51 (16.9%) patients in the CT-P13 and infliximab arms, respectively. 15 (5%) CT-P13-treated and 17 (6%) infliximab-treated patients experienced at least 1 infusion reaction. Tuberculosis was reported in 3 patients in the CT-P13 arm and in 1 patient in the infliximab arm. Conclusions: CT-P13 and infliximab are equivalent in terms of ACR20 in patients with RA. In addition, CT-P13 was well tolerated, with an efficacy and safety profile comparable to that of infliximab up to week 30. Disclosure of Interest: D. Yoo: None Declared, P. Miranda: None Declared, M. Piotrowski: None Declared, E. Ramiterre: None Declared, V. Kovalenko: None Declared, N. Prodanovic: None Declared, M. Tee: None Declared, S. Gutierrez-Ureña: None Declared, R. Jimenez: None Declared, O. Zamani: None Declared, S. Lee: None Declared, H. Kim Employee of: Celltrion, W. Park: None Declared, U. Müller-Ladner: None Declared